A Computational Approach to Learning Music - Merchant, Siddh; Jain, Reetu (iJournals:International Journal of Software & Hardware Research in Engineering ISSN:2347-4890, 2022)
Learning the guitar is not an easy task, several people have tried methods like online lessons and even physical ones, yet progress is slow. Due to the above, most quit whilst others find marginal levels of success. Research has been conducted to design a different approach to learning and practicing the guitar. Its purpose is to establish a system in which a user can create music without having to explore the intricacies of music theory, making the task easier and thus more achievable for the general population. By doing so, it strives to make music a more approachable domain for those who wish to explore it. In the process, I devised a unique way of approaching the instrument; one that avoids theory and draws focus on musical sense. Using open CV and python, I designed a program that takes scales as inputs and provides a harmonious sequence of notes as an output. Although based on the guitar, the theory explored in the project can be applied to any fretted instrument that holds a discrete set of notes. Using this program, general users can have access to instruments and consequently the benefits associated with playing music. This opens doors to music therapy and exercises used to focus/develop certain parts of the brain.